Four-Dimensional Image-Guided Adaptive Brachytherapy for Cervical Cancer: A Systematic Review and Meta-Regression Analysis - Li, Fei; Shi, Dan; Bu, Mingwei; Lu, Shuangchen; Zhao, Hongfu (Frontiers in Oncology, 2022)
Purpose: The ICRU/GEC-ESTRO released the ICRU Report No. 89, which introduced the concept of four-dimensional brachytherapy and ushered in a new era of brachytherapy for cervical cancer. The purpose of this study was to evaluate the local control and late toxicity of four-dimensional brachytherapy in cervical cancer through a systematic review and to reveal the dose-response relationship between the volumetric dose paraments and the local control rate via a probit model. Material and methods: We identified studies that reported the HR-CTV D90 and local control probabilities by searching the PubMed Database, the Web of Science Core Collection and the Cochrane Library Database through February 1st, 2022. Regression analyses were performed between the HR-CTV D90 and the local control probability using a probit model. Results: Nineteen studies enrolling 3,616 patients were included. The probit model showed a significant relationship between the HR-CTV D90 value and IR-CTV D90 Vs. the local control probability, P < 0.001 and P = 0.003, respectively. The D90 for HR-CTV and IR-CTV corresponding to a probability of 90% local control was 79.1 GyEQD2,10 (95% CI:69.8 – 83.7 GyEQD2,10) and 66.5 GyEQD2,10 (95% CI: 62.8 - 67.9 GyEQD2,10), respectively. The limits for the prescribed dose of 85 GyEQD2,10 for HR-CTV D90 theoretically warranted a 92.1% (95% CI: 90.2% - 95.3%) local control rate, and 87.2% (95% CI: 82.4% - 91.8%) local control probability was expected for 65 GyEQD2,10 to IR-CTV D90. The probit model showed no significant relationship between the D2cc to organs at risk and the probability of grade 3 and above gastrointestinal or genitourinary toxicity. Conclusions: Four-dimensional brachytherapy takes into account uncertain factors such as tumour regression, internal organ motion and organ filling, and provides a more accurate and more therapeutic ratio delivery through adaptive delineation and replanning, replacement of the applicator, and the addition of interstitial needles. The dose volume effect relationship of four-dimensional brachytherapy between the HR-CTV D90 and the local control rate provides an objective aim dose.